A 24-year longitudinal study on a STEM gateway general chemistry course and the reduction of achievement disparities - Partha Basu; David J. Malik; Steven Graunke (PLoS ONE, 2025)
The “First Year Experience” is a critical component of retention of STEM majors. Often, general chemistry has been labeled as a “gatekeeper” course for STEM careers due to a high attrition rate and a course that leads to increased time for graduation when students are inadequately prepared. We demonstrate that the active learning strategy Peer-Led Team Learning (PLTL) model increases student retention (%DFW calculated from earned grades A through F plus withdrawals, W) and success (%ABC calculated from earned grades A through F). We have analyzed approximately 24 years of data in general chemistry I (~20,000 students), using Analysis of Covariance (ANCOVA), which showed progressive, significant improvement in both student success and completion metrics. A Hierarchical Linear Modeling (HLM), using a combination of course and student-level variables, demonstrated the impact of PLTL on internal exam metrics and overall course grades. Further, HLM modeling assessed the impact of PLTL controlling for various student demographics. PLTL strongly impacted URM student completion rates to a greater degree than well-represented students, reducing the URM/non-URM achievement gap.